Pre-, Co-, and Post-Failure Deformation Analysis of the Catastrophic Xinjing Open-Pit Coal Mine Landslide, China, from Optical and Radar Remote Sensing Observations - Fengnian Chang; Houyu Li; Shaochun Dong; Hongwei Yin (Remote Sensing)
Landslide risks in open-pit mine areas are heightened by artificial slope modifications necessary for mining operations, endangering human life and property. On 22 February 2023, a catastrophic landslide occurred at the Xinjing Open-Pit Coal Mine in Inner Mongolia, China, resulting in 53 fatalities and economic losses totaling 28.7 million USD. Investigating the pre-, co-, and post-failure deformation processes and exploring the potential driving mechanisms are crucial to preventing similar tragedies. In this study, we used multi-source optical and radar images alongside satellite geodetic methods to analyze the event. The results revealed pre-failure acceleration at the slope toe, large-scale southward displacement during collapse, and ongoing deformation across the mine area due to mining operations and waste accumulation. The collapse was primarily triggered by an excessively steep, non-compliant artificial slope design and continuous excavation at the slope’s base. Furthermore, our experiments indicated that the commonly used Sentinel-1 Interferometric Synthetic Aperture Radar (InSAR) significantly underestimated landslide deformation due to the maximum detectable deformation gradient (MDDG) limitation. In contrast, the high-spatial-resolution Fucheng-1 provided more accurate monitoring results with a higher MDDG. This underscores the importance of carefully assessing the MDDG when employing InSAR techniques to monitor rapid deformation in mining areas.